Analisis Faktor Kinerja Keuangan Implikasinya Terhadap Stabilitas Keuangan Dimana Kepemilikan Publik Sebagai Mediasi - Tedy Permana; Aang Syahdina; Keri Boru Hotang (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
This study chose a single stage sampling procedure, and based on the existing criteria obtained a sample of 9 companies for Construction & Housing Services. The analytical method in this study uses panel data with the help of the Eviews 9 program. The results of this study indicate that there is no significant effect of profitability on public ownership. There is an effect of liquidity on public ownership. There is no effect of long-term debt on public ownership. There is an effect of activity on public ownership. There is an effect of profitability (ROA), liquidity (CR), long-term debt (DER), activity (WCT) on public ownership. There is no significant effect of profitability on financial stability. There is a significant positive effect of liquidity on financial stability. There is no effect of long-term debt on financial stability. There is no effect of activity on financial stability. There is an effect of public ownership on financial stability. There is an effect of profitability (ROA), liquidity (CR), long-term debt (DER), activity (WCT) and public ownership (KP) on the financial stability of the Construction & Housing Services sub-sector companies on the IDX.